Feasibility study of reverse trilateration strategy with a single Tx for VLP - Chaudhary, Neha (2021)
This paper describes a visible light position system relying on a single transmitter to infer position information. The system adopts a reverse trilateration scheme, where a set of three photodiodes is employed to estimate the position. The reverse trilateration scheme adopted for this system, yields to a very simple mathematical framework, suitable for low power and low complexity systems. The position information is inferred through Rx signal strength, without the need for sophisticated angle measurements or precise synchronization as is the case in angle of arrival and time difference of arrival systems. Simulation results show that the proposed system shows high susceptibility to noise, thus requiring high signal to noise ratios in order to achieve low positioning errors.